Retrieval of Embolized Atrial Septal Defect Device from Left Atrium using Innovative Techniques - Mehmood, Amjad; Imtiaz, Sana; Akhtar, Khurram; Sadiq, Nadeem (Pakistan Armed Forces Medical Journal, 2022)
We report a technically difficult retrieval of embolized Atrial Septal Defect device from left atrium. Device was captured after multiple attempts using different types of snares and was brought to inferior vena cava without delivery sheath. As we were unable to slenderize the device into short sheath, it was finally retrieved using an unconventional and innovative technique.We emphasize the importance of safe improvised methods during challenging catheterization procedures resulting in successful outcomes.